KENDALA PENYELESAIAN HUKUM TERHADAP PERMASALAHAN KREDIT MACET PERBANKAN MELALUI PENYELESAIAN LITIGASI - , Bayu Setyo Pratomo ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aimed to determine the process of litigation against bank bad credit problem, causes of bad credit banking litigation. The data used inthe form of secondary data. From the analysis it is known that the process of settlement of bad loans made by the court that the district court made by filing a breach of contract to the distrik court and its processes a well as in civil procedural law in general,which includes charge, verivication, and then based on the evidence given decision, while decision may be appealed if there is a disgruntled party. The causes of the settlement of bad debts through the courts is because it takes a long time from the completion of the court of first instance, appeal, appeal or judicial review. Not all judgment to do execution, it is considering the longer a dispute resolution then changes the state of the influential example is the condition of the debtor that are increasingly entangled so that the economic downturn cannot repay loans.